To tweet or not to tweet : writing effective text messages for business - Canavor, Natalie, 1942- (Pearson Education Pub. as FTPress Delivers, 2010)
"This Element is an excerpt from The Truth About the New Rules of Business Writing (ISBN: 9780137153152) by Natalie Canavor and Claire Meirowitz. Increasingly, large organizations are finding an active Twitter "presence" essential to branding and customer interface. If you're an entrepreneur, a professional, or a consultant, Twitter can be great for your purposes, too. But super-speeding the delivery system does not mean you should short-shrift the writing process. On the contrary: Look at texting and tweeting as the ultimate self-edit--a sort of final writing exam"--Resource description page.